Prevalence of tuberculosis in silicosis patients in southern part of Rajasthan - Luhadia, Atul; Luhadia, Shanti Kumar; Ahluwalia, Rahul; Singh Arora, Kamal Preet; Kumar, Rahul; Nagda, Trishi; Zota, Adit (International Journal of Research in Medical Sciences, 2020)
Background: Silicosis is an occupational lung disease which commonly occurs in workers involved in quarrying, mining, sandblasting etc. Tuberculosis (TB) in silicosis is more common. In southern part of Rajasthan, near Udaipur a lot of mining areas are there and workers are exposed to silica dust. The main objective of carrying out this study is to bring in focus the increasing prevalence of silicosis patients and its complications in mining areas around Udaipur in southern Rajasthan, so that the necessary prophylactic and preventive measures can be taken for the workers in future. Methods: 150 patients of silicosis and old treated case of silicotuberculosis patient with respiratory symptoms were included in the study. In all the patients, sputum was sent for routine acid fast bacilli (AFB) smear examination and if it came negative then sputum was sent for GeneXpert multidrug resistant tuberculosis (MTB) and also for AFB culture examination wherever needed. Results: The mean duration of exposure to silica particles was 10 years (5 to 15 years). Tuberculosis was diagnosed by microbiological examination in 40 cases, while 25 cases which were previously treated for tuberculosis were found negative on microbiological examination. So, the overall prevalence of TB (both old treated and new or relapse microbiologically confirmed cases) among patients of silicosis was found to be 44%. Conclusions: Our study showed an increased prevalence of tuberculosis in silicosis patients. So, there should be regular health check up educational programme for all silica mines workers and all should use prophylactic measures.